DEVELOPMENT OF STUDENT WORKSHEET ON PROTOZOA MATERIAL FOR MASTERY OF CONCEPTS AND CRITICAL THINKING SKILLS AT SEKOLAH MENENGAH PERTAMA NEGERI 16 MEDAN - Atika; Mufti Sudibyo; Idramsa (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The development of this student worksheet was driven by the need for guided discovery-based worksheets in protozoa practicum activities to enhance students’ concept mastery and critical thinking skills. This study aimed to determine the feasibility, practicality, and effectiveness of the developed worksheet. The research employed the ADDIE model and involved data collection through interviews and questionnaires, followed by both quantitative and qualitative descriptive analysis. The subjects of the study were students and teachers of Sekolah Menengah Pertama Negeri 16 Medan. The results showed that the feasibility test of student work sheet material obtained 87% and media 95% after product revision. For the practicality test, the teacher's response was 97% and students 94%. The effectiveness test shows that N-Gain on the concept mastery variable is 0.7563 (75.63%) and on critical thinking skills is 0.7705 (77.05%) and both are in the high and effective categories. This value shows that student work sheet not only helps understanding the material but also improves concept mastery and critical thinking skills. It can be concluded that the student work sheet developed is very feasible, practical and effective to use in learning.